2006
DOI: 10.1038/sj.jp.7211500
|View full text |Cite
|
Sign up to set email alerts
|

Pulse oximetry in very low birth weight infants: can oxygen saturation be maintained in the desired range?

Abstract: Objective: To determine if a change in the pulse oximeter goal range and high alarm limit for oxygen saturation (SpO 2 ) alters the distribution of SpO 2 for premature infants in oxygen.Study design: This was a prospective, observational analysis. For group 1 (February 2002 to April 2002, n ¼ 23), pulse oximeter alarms were set at 80% (low) and 96% (high), and the goal range was 90-95%. For group 2 (May 2002 to August 2003, n ¼ 49), the high alarm was lowered to 94%, and the goal range was 88 to 94%. The SpO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 19 publications
3
59
3
1
Order By: Relevance
“…We were unable to analyze bronchopulmonary dysplasia, or other elements of care process examined in SUPPORT (ie, targeted ventilation strategy and oxygen saturation), which were not included in the PMH databases. In addition, target oxygen saturation values of 88% to 94%, a PMH NICU policy since May 2002, 37 …”
Section: Discussionmentioning
confidence: 99%
“…We were unable to analyze bronchopulmonary dysplasia, or other elements of care process examined in SUPPORT (ie, targeted ventilation strategy and oxygen saturation), which were not included in the PMH databases. In addition, target oxygen saturation values of 88% to 94%, a PMH NICU policy since May 2002, 37 …”
Section: Discussionmentioning
confidence: 99%
“…In Colombia, SpO 2 was within or above the target 34 and 55% of the time, respectively 21. Effects of training nurses to target SpO 2 ranges are varied 23, 27…”
mentioning
confidence: 99%
“…12 Studies that compare actual versus intended pulse oxygen saturation in very preterm infants have shown that poor compliance with the desired range of oxygen saturation target values and with alarm limits for pulse oximetry is an important and common problem in NICUs worldwide. [13][14][15][16][17] However, our neonatal team has maintained COT study participants within the intended pulse oximetry alarm limits between 68 and 79% of the time. Although our teams' performance is among the best of all neonatal units participating in the COT study, it needs to be highlighted that we only measured compliance during the first 3 days of life while infants were receiving supplemental oxygen.…”
Section: /41mentioning
confidence: 99%